2021
DOI: 10.3390/ijerph18094692
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Availability and Accessibility of Rehabilitation Services in a Rural District of South Africa: A Mixed-Methods Study

Abstract: Introduction: Rehabilitation services aim to optimise individuals’ functioning and reduce disability. However, people with disabilities, who represent a key population of users of rehabilitation services, continue to have unmet needs for rehabilitation services that include the provision of assistive devices. This paper examines the availability and accessibility of rehabilitation services in a rural district of South Africa in order to explore why unmet needs for rehabilitation services persist. Methods: All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…However, only a limited range of therapeutic options exist in most LMIC settings. A 2021 study of rehabilitation services across nine hospitals in one rural South African district found that patients’ needs were not met because of a lack of assistive devices that could be used for mobility training, such as walkers, canes, wheelchairs, and ankle braces, resulting in very limited rehabilitation options and compromising patients’ recovery potential 11 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…However, only a limited range of therapeutic options exist in most LMIC settings. A 2021 study of rehabilitation services across nine hospitals in one rural South African district found that patients’ needs were not met because of a lack of assistive devices that could be used for mobility training, such as walkers, canes, wheelchairs, and ankle braces, resulting in very limited rehabilitation options and compromising patients’ recovery potential 11 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…Finally, there is evidence that the development of multi-disciplinary specialized care centers to manage post-MI and stroke patients leads to improved outcomes ( 71 ). Multi-disciplinary specialized care centers have been successfully implemented in some parts of the African region ( 72 ) and it is important that such efforts are scaled up throughout the continent.…”
Section: Overview Of Cardiovascular Pathologies In Africamentioning
confidence: 99%
“…Visagie and Swartz ( 2016 ), as well as Magaqa, Ariana and Polack ( 2021 ), confirmed these rehabilitation challenges in their recent studies. The difficulties often experienced by persons with disabilities include service accessibility and/or inaccessible physical or built environment; receiving lower-quality services and added extra costs for healthcare services (Kuper & Heydt 2019 ); discrimination and social stigma (Hashemi et al 2020 ; Mitchell et al 2022); and knowledge, information and communication barriers (Hashemi et al 2020 ; Mitchel et al 2022).…”
Section: Introductionmentioning
confidence: 57%